Implementasi Model Blended Learning pada Mahasiswa PGSD di Universitas Bina Nusantara - Rina Patriana Chairiyani; Dasim Budimansyah; Kama Abdul Hakam; Yadi Ruyadi (Elementary Teacher Education Program, Majalengka University, 2023)
Blended learning is a learning method that integrates face-to-face learning and online learning. This research aims to investigate the implementation of the blended learning model in Primary School Teacher Education (PGSD) students at Bina Nusantara University. By focusing on aspects of curriculum, technology, and student-teacher interaction, this research reveals the impact and effectiveness of this model on student learning experiences. This research used a qualitative approach with an open questionnaire method. Data was collected from teachers and students involved in the PGSD program. The research results show that the implementation of the blended learning model has provided significant benefits in enriching material, developing technology skills, and student engagement. However, the research results also highlight several challenges, including access to technology, lack of training for teachers, and effective time management. This research provides valuable insight into the successes and obstacles of implementing the blended learning model for PGSD students at Bina Nusantara University. This study provides recommendations for improving the quality of the blended learning model by considering the needs and characteristics of PGSD students. The results of this research can be a guide for higher education institutions in designing, implementing and improving blended learning methods to support quality education in the future.